Relations of features of companies and their R&D activities - Pekk, Letícia; Kovács, Zoltán; Háry, András (Vezetéstudomány / Budapest Management Review, 2025)
Understanding and enhancing the innovation capabilities of technology-oriented businesses is especially important in Central and Eastern European countries, where increasing productivity is a primary goal. This article examines the relationship between company characteristics – such as size, ownership structure, and location – and features of their research and development activities, including defined objectives and applied methods. The study uses data from 102 technology-oriented industrial production, service, and development companies, gathered through publicly available statistics, personal interviews, and observations, and analyzed using statistical methods like cross-tabulation analyses, statistical tests, similarity and pattern analyses, and machine learning. Nearly half of the companies reported experimental development as an R&D activity, while smaller process innovations occurred in each ownership categories. The results show that ownership relationships play a decisive role in certain research and development activities among the companies surveyed. A strong relationship was found between international ownership and technological development.